Differential responses of two cyanobacterial species to R-metalaxyl toxicity: Growth, photosynthesis and antioxidant analyses. (March 2020) - Hamed, Seham M.; Hassan, Sherif H.; Selim, Samy; Wadaan, Mohammed A.M.; Mohany, Mohamed; Hozzein, Wael N.; AbdElgawad, Hamada
Abstract: Metalaxyl is a broad-spectrum chiral fungicide that used for the protection of plants, however extensive use of metalaxyl resulted in serious environmental problems. Thus, a study on the detoxification mechanism in algae/cyanobacteria and their ability for phycoremediation is highly recommended. Here, we investigated the physiological and biochemical responses of two cyanobacterial species; Anabaena laxa and Nostoc muscorum to R -metalaxyl toxicity as well as their ability as phycoremediators. Two different levels of R- metalaxyl, at mild (10 mg/L) and high dose (25 mg/L), were applied for one-week. We found that A. laxa absorbed and accumulated more intracellular R- metalaxyl compared to N. muscorum . R- metalaxyl, which triggered a dose-based reduction in cell growth, photosynthetic pigment content, and photosynthetic key enzymes' activities i.e., phosphoenolpyruvate carboxylase (PEPC) and ribulose‒1, 5‒bisphosphate carboxylase/oxygenase (RuBisCo). These decreases were significantly less pronounced in A. laxa . On the other hand, R -metalaxyl significantly induced oxidative damage markers, e.g., H2 O2 levels, lipid peroxidation (MDA), protein oxidation and NADPH oxidase activity. However, these increases were also lower in A. laxa compared to N. muscorum. To alleviate R -metalaxyl toxicity, A. laxa induced the polyphenols, flavonoids, tocopherols and glutathione (GSH) levels as well as peroxidase (POX), glutathione peroxidase (GPX), glutathione reductase (GR) and glutathione-s-transferase (GST) enzyme activities. On the contrary, the significant induction of antioxidants in N. muscorum was restricted to ascorbate, catalase (CAT) and ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR) enzyme activities. Although A. laxa accumulated more R- metalaxyl, it experienced less stress due to subsequent induction of antioxidants. Therefore, A. laxa may be a promising R- metalaxyl phycoremediator. Our results provided basic data for understanding the ecotoxicology of R -metalaxyl contamination in aquatic habitats and the toxicity indices among cyanobacteria. Graphical abstract: Image 1 Highlights: R- metalaxyl-induced toxicity in cyanobacteria was a function of dose and species type. Although Anabaena laxa accumulated R- metalaxyl, it experienced less stress than Nostoc muscorum. R- metalaxyl induced photosynthesis inhibition and oxidative damage which were less pronounced in A. laxa . Our analyses implicated the role of antioxidant defence system in R- metalaxyl stress tolerance in A. laxa. A. laxa is a promising species for R- metalaxyl phycoremediation. Abstract : Main finding: R- metalaxyl-induced toxicity in cyanobacteria was a function of dose and species type. Although Anabaena laxa accumulated more R- metalaxyl, it experienced less stress due to its antioxidant defense system. A. laxa may be a promising R- metalaxyl phycoremediator.